Effectiveness of the integration of SPT-Drill and imagery training methods: A treatment to beat target panic in archery - Priambudi, Muhammad Amin; Mashud,; Arifin, Syamsul (Journal Sport Area, 2023)
Background Problems: Target panic was an experience that almost all archers went through. Research Objectives: This study aimed to minimise the symptoms of target panic in archery, including flinching, punching, freezing, and snap-shooting, by implementing the integration of the Specific Physical Training (SPT) Drill method with imagery. Methods: In this context, the method used is sports action research with the Kurt Lewin model, which consists of planning, implementation, observation, and reflection. The subjects were NPCI Kalsel Para-Archery athletes, totaling 12 athletes consisting of 9 males and 3 females. The data analysis used is descriptive-quantitative. Findings and Results: The study revealed an improvement in effectively managing panic-inducing events using the implemented method. In the initial cycle, 41.67% (5 athletes) achieved success in controlling panic, falling below the criteria. However, in the second cycle, there was a notable enhancement, reaching a success rate of 83.33% (10 athletes), meeting criteria. In the second cycle, proficiency levels showed a remarkable increase of 99.98% and a decrease of 28.58%. Conclusion: By demonstrating the effectiveness of integrating the SPT drill with imagery in alleviating target panic, this research makes a noteworthy contribution to the literature on sports psychology and archery training. The results highlight the appropriateness of this approach in improving archers' physical conditioning, fostering confidence, and subtly reshaping their perspectives on anxiety related to archery. We can say that the SPT drill with imagery worked because it got better every time from the first cycle to the next. This shows that it could be a good way to help archers who get target panic.